COL6A6 Peptide Vaccine Alleviates Atherosclerosis through Inducing Immune Response and Regulating Lipid Metabolism in Apoe−/− Mice - Dongmei Tang; Yan Liu; Rui Duan; Run Lin; Zhonghao Li; Xianyan Liu; Jingrong Huang; Ming Zhao (Cells, 2024)
Atherosclerosis is an autoimmune disease characterized by lipid imbalances and chronic inflammation within blood vessels, with limited preventive and treatment options currently available. In this study, a vaccine prepared with COL6A6 peptide (named the Pep_A6 vaccine) was administered to immunize Apoe−/− mice, and the immune mechanism of the Pep_A6 vaccine against atherosclerosis was first investigated. The results of arterial oil red O staining demonstrated that the Pep_A6 vaccine significantly reduced the atherosclerotic plaque area in Apoe−/− mice fed with a high-fat diet for 20 weeks. A flow cytometry analysis revealed that the Pep_A6 vaccine inhibited Th1 cell differentiation and increased the proportion of Treg cells. Furthermore, there was a significant increase in Ly6Clow monocytes observed in the vaccinated group. The ELISA results showed that the Pep_A6 vaccine induced a significant expression of Pep_A6-specific antibody IgG and IgG1 in mouse serum. Additionally, we found that the Pep_A6 vaccine significantly decreased serum LDL-C content and regulated the expression of genes related to liver lipid metabolism. Together, our findings suggest that the Pep_A6 vaccine alleviates atherosclerosis by inducing a positive immune response and regulating lipid metabolism, providing new insights into potential prevention strategies for atherosclerosis as an innovative vaccine.